2022
DOI: 10.1111/cas.15538
|View full text |Cite
|
Sign up to set email alerts
|

The oral bacterium Streptococcus mutans promotes tumor metastasis by inducing vascular inflammation

Abstract: Recent studies have demonstrated a relationship between oral bacteria and systemic inflammation. Endothelial cells (ECs), which line blood vessels, control the opening and closing of the vascular barrier and contribute to hematogenous metastasis; however, the role of oral bacteria‐induced vascular inflammation in tumor metastasis remains unclear. In this study, we examined the phenotypic changes in vascular ECs following Streptococcus mutans (S. mutans) stimulation in vitro and in vivo. The expression of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Interestingly, our histological findings were inconsistent with the results of others in that whether S. mutans could induce significant histopathological changes or not in vivo animal study. For example, by infection with S. mutans, Velusamy et al demonstrated the infiltrated with inflammatory cells and abnormal structures of the lung alveoli with thickening alveolar walls in lung tissues; prominent accumulation of lipids and macrovesicular appearance along with ballooning and vacuolization of hepatocytes and significant infiltration of inflammatory cells in liver, and splenomegaly and infiltrations of increasing inflammatory cells in spleen specimen (Kim et al, 2012;Hong et al, 2014;Naka et al, 2014;Velusamy et al, 2014;Naka et al, 2016;Yu et al, 2022). However, the duration of bacterial infection was much longer in those studies, and this helped to explain the inconsistent results partly.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our histological findings were inconsistent with the results of others in that whether S. mutans could induce significant histopathological changes or not in vivo animal study. For example, by infection with S. mutans, Velusamy et al demonstrated the infiltrated with inflammatory cells and abnormal structures of the lung alveoli with thickening alveolar walls in lung tissues; prominent accumulation of lipids and macrovesicular appearance along with ballooning and vacuolization of hepatocytes and significant infiltration of inflammatory cells in liver, and splenomegaly and infiltrations of increasing inflammatory cells in spleen specimen (Kim et al, 2012;Hong et al, 2014;Naka et al, 2014;Velusamy et al, 2014;Naka et al, 2016;Yu et al, 2022). However, the duration of bacterial infection was much longer in those studies, and this helped to explain the inconsistent results partly.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from nonstimulated and S. mutans ‐stimulated MS1 cells using the Relia‐Prep RNA Miniprep System, followed by quality identification using an RNA 6000 Nano Assay Kit and a 2100 Bioanalyzer (Agilent Technologies). Subsequently, next‐generation sequencing for RNA‐seq was carried out by Takara Bio Inc. as previously reported 1 . Pathway analysis was undertaken using IPA software (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse lung inflammation and lung tumor metastasis models with or without aspirin therapy were created using 6‐week‐old female C57BL/6 mice purchased from CLEA Japan as previously reported 1 . The lung inflammation model was created by intravenous implantation of 1 × 10 5 CFUs of S. mutans suspensions into the mouse tail vein every 2 days for a total of eight injections (PBS implantation as a control), and the mice were killed 1 day after the final implantation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations